Impacts of capacitive current on electrolyte-gated graphene field-effect transistor arrays - Shota Ushiba; Tomomi Nakano; Yuka Tokuda; Shinsuke Tani; Masahiko Kimura; Kazuhiko Matsumoto (Applied Physics Express)
We investigate the effect of gate-source current ( I _GS ) on variations in the Dirac point voltage ( V _DP ) in electrolyte-gated graphene field-effect transistor (EG-GFET) arrays through a time-resolved analysis of I _GS and an equivalent circuit model. Source/drain electrodes exposed to the electrolyte induce a substantial capacitive current and a prolonged charging duration of the electric double-layer capacitance, which leads to a position-dependent V _DP variation relative to the gate electrode. The electrode-passivation alleviates the variation by significantly reducing I _GS and associated charging time. These findings offer critical insights for the design of integrated EG-GFET arrays.